The rebel wife - Polites, Taylor, 1970- (Simon & Schuster, 2012)
Forced into marriage with a wealthy man after her Southern family is rendered destitute by the Civil War, Augusta becomes a widow a decade later and finds her circumstances hinging on a missing package in a community torn by racial prejudice, violence, and disease.